Rehabilitation Versus no Intervention – Only a Continued Intensive Program Conducted Statistically Significant Improvements Motor Skills in Parkinson's Disease Patients - Calvo, Jesús Seco; Fernández, Inés Gago (IntechOpen, 2011)
None